The Use of Virtual and Augmented Reality in Law Enforcement Training: An Interdisciplinary Review of Current Approaches and Empirical Findings (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The study examines the use of virtual and augmented reality technologies in the professional training of security sector employees, in particular law enforcement officers. It is noted that the introduction of immersive technologies into the training system of the Ministry of Internal Affairs of Ukraine and the National Guard of Ukraine is particularly relevant in the context of martial law and the transformation of the security environment.The experience of foreign countries and Ukraine in the use of virtual and augmented reality technologies in training programmes for preparation for actions in stressful, crisis and combat situations is analysed. It is determined that the use of such technologies contributes to the formation of stress resistance, the development of reflective thinking, teamwork skills and communicative flexibility.The methodological basis of the study consists of systematic and comparative methods, content analysis of scientific and practical sources, as well as a summary of international experience in the implementation of virtual and augmented reality technologies in the training of police officers and military personnel in the United States, Canada, European Union countries, Israel, the United Arab Emirates, and Ukraine.The scientific novelty of the study lies in the systematisation of international experience in the use of immersive technologies in the training of law enforcement officers and the development of an author's methodological scheme for the integration of virtual and augmented reality technologies into the professional education system of the security sector in Ukraine.The results of the study can be used to create a national methodological base for virtual and augmented reality technologies in education, develop training programmes and train instructors in the use of immersive technologies.It was concluded that training using virtual and augmented reality technologies increases the effectiveness of decision-making in crisis situations, reduces the risk of professional burnout, and contributes to the formation of professional readiness of law enforcement officers to act in conditions of uncertainty and danger. It is emphasised that the integration of such technologies into the training of law enforcement officers is a strategic direction for the development of security education in Ukraine, which requires adequate scientific, methodological, technical and institutional support.